1991
DOI: 10.1177/153857449102500810
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Cystic Hydatids Causing Cardiac Tamponade—Report of Cases

Abstract: Four patients with cystic hydatids located in pericardium and myocardium were admitted. Cardiac tamponade was determined in 1 of these cases. Surgical treatment was instituted for all cases. Transpericardial cardiac palpation was emphasized in cases where thoracotomy was necessary due to the lung cystic hydatids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2000
2000

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Cardiac involvement in hydatidosis has been reported with a frequency in the range of 0.2% to 3%. [1][2][3][4][5] Cardiac hydatid cysts are more often seen in the left ventricle, presumably because blood flow is higher than in the right ventricle. [2][3][4][5] Signs and symptoms of such cysts are due to their location, growth, and rupture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiac involvement in hydatidosis has been reported with a frequency in the range of 0.2% to 3%. [1][2][3][4][5] Cardiac hydatid cysts are more often seen in the left ventricle, presumably because blood flow is higher than in the right ventricle. [2][3][4][5] Signs and symptoms of such cysts are due to their location, growth, and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anthelmintics (mebendazole or albendazole) should be given in the postoperative period because of the risks of vesicular implantation and embolization. [1][2][3][4] Although cardiac involvement of hydatid disease is rare even in endemic areas, this case study suggests that echocardiographic evaluation should be performed in patients with hydatid cysts elsewhere in the body. This useful workbook is dedicated to Bhagawan Sri Sathya Sai Baba who has been an inspiration in the treatment of patients in the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydatid cyst disease is endemic in sheep-raising countries, but cardiac involvement is rare, occurring in less than 2% of cases [1]. In Turkey, in a series of 600 pulmonary hydatid cysts, the heart was involved in only four patients [2]. When cardiac involvement occurs, it is mainly myocardial.…”
Section: Introductionmentioning
confidence: 99%